The Assessment on the Importance of Baking Skills and Learning Enhancement of Hospitality Management Students on Bestlink College of the Philippines: Basis for Recommendation: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The hospitality industry is an innovative and very competitive one. The students can alsospecialize in other areas of the industry, from guest services to events planning and culinaryservices. Every year, baking evolves and innovates, and it has its trends, like new flavors, newstyles, and ways of making it. Hospitality management students encountered problems inenhancing their baking skills and gaining knowledge using the bread and pastry laboratory,and this study wants to help in adjusting time and renovating the laboratories for the benefit ofthe students and school administration.The findings show that students are highly beneficial in having entrepreneurial, enhancingtheir creativity, teamwork, and problem-solving skills in the workplace, and also in developingtheir technical skills. The results also show that the bread and pastry laboratory is functionalfor students to use when practicing their baking skills. There are factors that can affectlearning enhancement in practicing baking skills of the students in the bread and pastrylaboratory, and this study can help to make adjustments of time and renovate the laboratoriesfor the future students of Bestlink College of the Philippines.The researchers came out with the recommendation that professional teachers of the BSHMmust always be hands-on in guiding and be attentive to the development of the students'baking skills. The school administration should adjust the time allotted to the students in everylaboratory simulation and in practicing their baking skills. The researchers also recommendthat the school administration renovate the bread and pastry laboratory to make more spacefor students who are using the laboratory and provide more storage lockers for student bagsand other personal belongings. Students must know the importance of being responsible inthe maintenance of the tools and equipment while using them in laboratories for futurestudents of BSHM.
Keywords: Business